A Comparative Study of the Effect of Massage with Sunflower Oil or Sesame Oil on Infants' Crying and Sleep Times: A Randomized Clinical Trial - Fatemeh Sadat Hosseini Baharanchi; Anooshirvan Kazemnejad; Shahnaz Golian Tehrani; Mandana Mirmohammadali; Bagher Minaee; Reza Bekhradi; Ziba Raisi Dehkordi (Tehran University of Medical Sciences, 2011)
Background & Aim: Infants are very sensitive and special attention is needed to take care of their physical and mental health. Some studies showed that massage by parents can improve infants sleep quality. The aim of this study was to compare the effect of massage with sunflower oil or sesame oil on infants crying and sleep times. Methods & Materials: This triple-blinded clinical trial was conducted on 120 infants who were 10-15 days old, full-term, single, exclusively breastfed and with no history of hospitalization. The infants were assigned randomly into three groups of sunflower oil massage, sesame oil massage and massage with no oils. Mothers administered 15 minutes of massage to their infants twice per day (morning and afternoon) for 28 days. Times of crying and sleep were measured by a parents information form at baseline, and at the end of the first, second, third, and fourth weeks of the study. Data were analyzed using the repeated measures ANOVA. Result: Within four weeks of following, decreasing pattern of infants crying time was not significant (P=0.18); however, the mean of crying time between the three groups was significant (P=0.007). The interaction effect of crying time and groups was not significant (P=0.18). Increasing pattern of infant sleep time was statistically significant in the fourth weeks of the following (P<0.001); however, the mean of sleep time between three groups was not significant (P<0.56). The interaction effect of sleeping time and groups was not significant (P<0.10). Conclusion: Since there were not statistical significant differences between the infants' crying and sleep times between the three groups, and despite the fact that increasing pattern of infants sleep time is a normal pattern, it is not possible to have a proper conclusion.